PEMBUATAN RENCANA ANGGARAN BIAYA BAGI BADAN USAHA MILIK DESA DI KABUPATEN TANGERANG - Taufik Raharjo; Agus Sunarya Sulaeman (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Village-owned enterprises (BUMDesa) are one of the priorities for using the Village Fund. BUMDesa was established in order to realize economic independence in rural areas. At present, all villages in Tangerang Regency have established BUMDesa, but there are still many who do not understand how to plan a budget. This business budget plan is very important in managing BUMDesa's finances. So the author discusses the need for knowledge and skills for BUMDesa managers in making budget plans to support their BUMDesa business development. The purpose of this community service activity is to increase knowledge and skills for BUMDesa managers in making budget plans for their respective businesses. This community service activity was in the form of training in making a budget plan that was followed by BUMDesa managers in the Tangerang Regency area. The result of this activity is an increase in understanding and skills in making a budget plan for their BUMDesa business.